Income inequality, capitalism and ethno-linguistic fractionalization - Jakob de Haan; Jan-Egbert Sturm (ETH Zurich, KOF Swiss Economic Institute, 2014)
We examine the relationship between capitalism and income inequality for a large sample of countries using an adjusted economic freedom index as proxy for capitalism and Gini coefficients based on gross-income as proxy for income inequality. Our results suggest that there is no robust relationship between economic freedom and income inequality. In addition, we analyze the relationship between income redistribution (measured by the ratio of the income distribution resulting from market processes and the income distribution after redistribution) and ethno-linguistic fractionalization. We find that the impact of ethno-linguistic fractionalization on income redistribution is conditional on the level of economic freedom: countries that have a high degree of fractionalization have less income redistribution, while capitalist countries that have a low degree of fractionalization have more income distribution.
Keywords: D31; D63; F02; O11; O15; 330; income inequality; redistribution; economic freedom; ethno-linguistic fractionalization